2008
DOI: 10.1634/theoncologist.2008-0181
|View full text |Cite
|
Sign up to set email alerts
|

High Concordance of KRAS Status Between Primary Colorectal Tumors and Related Metastatic Sites: Implications for Clinical Practice

Abstract: LEARNING OBJECTIVESAfter completing this course, the reader should be able to:1. Describe the importance of KRAS mutations in CRC patients.2. Explain the relevance to cancer treatment of concordance of KRAS status between primary tumors and metastases in CRC patients.3. Discuss the impact of KRAS mutations as a predictive/prognostic factor in CRC patients.This article is available for continuing medical education credit at CME.TheOncologist.com. CME CME ABSTRACTPurpose. Several studies have suggested that KRAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
123
1
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(148 citation statements)
references
References 22 publications
16
123
1
8
Order By: Relevance
“…Ten of the tested pair samples (45.5%) had a wt-KRAS genotype and 12 of the tested pair samples (55.5%) were KRAS mutation positive. In contrast to EGFR expression which may differ in primary colorectal tumor tissue and the corresponding metastatic tissue, literature reports high concordance between KRAS mutations of primary and metastatic tumors from patients with colorectal carcinoma (31,32). This grade of concordance is important from two aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten of the tested pair samples (45.5%) had a wt-KRAS genotype and 12 of the tested pair samples (55.5%) were KRAS mutation positive. In contrast to EGFR expression which may differ in primary colorectal tumor tissue and the corresponding metastatic tissue, literature reports high concordance between KRAS mutations of primary and metastatic tumors from patients with colorectal carcinoma (31,32). This grade of concordance is important from two aspects.…”
Section: Discussionmentioning
confidence: 99%
“…This grade of concordance is important from two aspects. Firstly it suggests that KRAS mutations are an early event in colorectal carcinoma pathogenesis and are not essential for metastatic spread of the tumor (31). Secondly, if the primary tumor sample is not available, the evaluation of KRAS mutational status can also be performed from a metastatic site with relatively high confidence.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a minority of the studies reported in this review used techniques other than sequencing. Additionally, most studies on concordance have carefully reviewed the quality and tumor content of the samples included in their analysis, and some studies performed sequencing twice, starting from different amplification reactions [28,31,53], whereas others had two independent observers to determine KRAS status [50,52], or re-evaluated their results using pyrosequencing [54]. Therefore, although it is possible that a small number of the discordant cases are a result of poor quality testing techniques, false test results are not likely to explain the discordant cases in the majority of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experience in colorectal cancer has established that KRAS mutations in the primary tumor and the metastatic lesions are identical, 84,85 simplifying patient characterization for cetuximab treatment. Conversely, lung cancer studies have demonstrated substantial differences between primary and metastatic sites.…”
Section: Correlation Between Primary Tumor and Metastases Alterationsmentioning
confidence: 99%